Frequency selective surface with complex topology elements - Mayboroda, D. V.; Pogarsky, S. A. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 2021)
Relevance: The solution of specific problems in modern technology of microwave and UHF ranges, such as the implementation of reducing the radar signature of objects, spatial frequency-selective filters, reflectors requires the development and creation of a special class of electrodynamic structures - frequency-selective surfaces. Due to the uniqueness of their electrodynamic characteristics, it is possible to solve quite technically complex problems - suppression of excited surface waves, the creation of "forbidden" zones in the amplitude-frequency characteristics.The purpose of the work is numerical modeling and experimental study of electrodynamic characteristics of plane frequency-selective surfaces with slotted elements of complex topology. Evaluation of the influence of the geometric parameters of the slot inhomogeneity and the material constants of the dielectric substrate on the reflection and transmission coefficients of the frequency-selective surface.Materials and methods: The paper presents the results of numerical simulation of the electrodynamic characteristics of a cell of an infinite 2D frequency-selective surface with the topology of a structural element -shaped and experimental studies of the prototype parameters. Modeling was performed within the framework of the finite element method (FEM) using the ANSOFT HFSS / ANSYS software product. Characteristic measurements are performed in free space by direct measurement of attenuation values.Results: In the course of numerical experiments, it was found that two types of resonances can arise in the structure, associated both with the ratio of the geometric dimensions of the structural element and with the presence of double-sided shielding. The influence of the thickness of the dielectric substrate and the values ​​of the dielectric constant on the reflection and transmission coefficients is investigated. The frequency dependences of the reflection value are established with a change in the spatial orientation of the structure relative to the incident wave front. The dependence of the magnitude of the radio transparency of a two-layer frequency-selective surface on the angle of rotation of the structure around a given axis has been established experimentally.Conclusion: The presented results of numerical simulation of the electrodynamic characteristics of a cell of an infinite 2D frequency-selective surface with the topology of a structural element -shaped and experimental studies have shown the possibility of spatial frequency selection. The totality of the results obtained makes it possible to predict the creation of sufficiently technological and highly efficient frequency-selective surfaces in the microwave range.